Teaching with MOOC: conducting programming courses for undergraduate students / Mohd Norafizal Abd Aziz, Haslinda Noradzan, Nor Zalina Ismail, Roslan Sadjirin - Abd Aziz, Mohd Norafizal; Noradzan, Haslinda; Ismail, Nor Zalina; Sadjirin, Roslan (UiTM Press, 2018)
Technologies adoption in learning has given opportunities that may support practitioners and learners as well as learning institutions to empower their learning implementation with the current technologies available. From e-learning concept towards the cloud learning implementation nowadays, it has shown significance of having technologies in learning implementation. For the practitioners views of implementation, technologies adoption will provide various platform of learning resources to be adopted by the practitioners to the learners to learn. As for the learners, the opportunities of having technology will help them in managing their individual learning platform. Instead, learners may use the technologies in learning to learn at anytime and anywhere with support by their own learning platform created.